2014
DOI: 10.1007/s00134-014-3468-4
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of hypothalamic–pituitary–adrenal axis hormones in early sepsis: a study performed in the emergency department

Abstract: Increased copeptin and HPA hormones baseline levels may provide crucial information for risk stratification in a variety of septic states in the ED. Furthermore, measurements of copeptin level and serum baseline cortisol concentration are promising independent prognostic markers for mortality in patients with severe sepsis or septic shock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
45
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 35 publications
7
45
3
Order By: Relevance
“…In contrast to our study, a large observational single‐center study from Beijing that included 461 patients admitted to the Emergency Department reported that copeptin levels might serve as an early diagnostic indicator of sepsis . Importantly, this study also noted an association between copeptin and disease severity as well as short‐term mortality in the Emergency Department setting .…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to our study, a large observational single‐center study from Beijing that included 461 patients admitted to the Emergency Department reported that copeptin levels might serve as an early diagnostic indicator of sepsis . Importantly, this study also noted an association between copeptin and disease severity as well as short‐term mortality in the Emergency Department setting .…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to our study, a large observational single‐center study from Beijing that included 461 patients admitted to the Emergency Department reported that copeptin levels might serve as an early diagnostic indicator of sepsis . Importantly, this study also noted an association between copeptin and disease severity as well as short‐term mortality in the Emergency Department setting . Our study that focused on critically ill patients at the ICU revealed that not the presence of sepsis, but the severity of critical illness as reflected by organ failure(s) and hemodynamic alterations was the main determinant for elevated copeptin.…”
Section: Discussioncontrasting
confidence: 98%
See 2 more Smart Citations
“…[10] Another study evaluating 461 patients admitted to the emergency department of a tertiary university hospital with signs of sepsis, demonstrated predictive abilities of copeptin levels at admission for the occurrence of septic shock and mortality. [18] In a small study evaluating 41 septic patients a strong correlation between copeptin and the disease severity score APACHE II was demonstrated. [19] In our cohort, only weak correlations between copeptin and APACHE II scores, as well as other established scores including the SAPS II and the SOFA score were demonstrated.…”
Section: Discussionmentioning
confidence: 99%